ANALYSIS AND OPTIMIZATION OF WORKSPACE FLEXIBILITY OF WELDING ROBOT - GAO Lu; SUN Bo; FU BaoDing (Jixie qiangdu)
To solve the problem of relative position installation between welding robot with welded parts,the workspace flexibility of the robot is analyzed. Firstly,the D-H method is used to model the kinematics of the robot,and the working space of the robot is solved by Monte Carlo method. Then,by means of the concept of service ball,a calculating method of flexibility suitable for the welding part is proposed,and the flexibility in the working space of the robot is solved. In the end,the influence of various parameters on the flexibility is analyzed,and through the genetic algorithm to optimize flexibility,the more flexibility of the robot workspace is obtained. This study provides a reference for the relative installation position between robot with welded parts and can ensure the reliability of welding.